An ultra-high performance concrete containing steel slag powder by using nano-silica and fiber interface modification, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611226605.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
但是使用钢渣粉却有着十分多的潜在问题
[0014]本发明提供了一种利用纳米二氧化硅及纤维界面改性的含钢渣粉的超高性能混凝土,包括如下组分:水泥、钢渣粉基材料、硅灰、石英砂、水、减水剂、改性钢纤维和纳米二氧化硅;所述水泥和钢渣粉基材料的质量比为1:(0.5~0.8);所述水泥和硅灰的质量比为1:(0.2~0.5);所述水泥和石英砂的质量比为1:(1.5~2);所述水泥和水的质量比为1:(0.3~0.4);所述水泥和减水剂的质量比为1:(0.02~0.03);所述水泥和改性钢纤维的质量比为1:(0.25~0.3);所述水泥和纳米二氧化硅的质量比为1:(0.03~0.05);所述钢渣粉基材料包括矿粉、钢渣粉和脱硫石膏;所述矿粉、钢渣粉和脱硫石膏的质量比为(50~60):(25~30):(10~20);所述改性钢纤维依次由退镀、表面羟基化和硅烷偶联剂KH550改性得到。本发明采用钢渣粉基材料大掺量代替水泥,降低混凝土成本,添加纳米二氧化硅,其能够与水泥水化产物中的氢氧化钙发生二次水化反应生成C-S-H凝胶,形成更致密的内部结构,同时纳米二氧化硅能够填充混凝土内部的微小空隙,提高混凝土的力学强度等性能;添加硅烷偶联剂改性钢纤维,硅烷偶联剂的“桥接”作用,一方面硅氧烷端水解后生成的硅醇能够与钢纤维表面的金属氧化物反应形成牢固的Si-O-Fe共价键,紧密牢固在纤维表面,另一方面有机官能团端可与水化产物发生化学反应或物理吸附,从而提高混凝土的性能,控制硅烷偶联剂的种类,采用KH550,其水解液为碱性溶液,反应活性更高,界面桥接能力更强,并且能够显著提高钢纤维表面粗糙度和附着力,相比于其他偶联剂,具有更好的改性效果;控制混凝土的组成和各组分的用量,在钢渣粉基材料等固废大掺量的情况下,提高混凝土的力学强度、耐高温性能和耐久性能。
Smart Images

Figure CN123003241A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to an ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface, its preparation method and application. Background Technology
[0002] Traditional ultra-high performance concrete (UHVPC) requires a large amount of cement, resulting in high costs and making it unsuitable for large-scale applications. Furthermore, the large amounts of steel slag generated during crude steelmaking can severely impact the local ecological environment if accumulated. Reusing steel slag powder, after grinding, as a cementitious material to prepare UHVPC significantly solves the problems of high costs, resource waste, and environmental pollution. However, the use of steel slag powder presents several potential challenges. The components in steel slag powder that can participate in hydration reactions are limited, and a large-scale replacement of cement inevitably leads to a decrease in mechanical strength. While steel fibers are typically incorporated to improve the mechanical strength of concrete, the inert oxides on the surface of steel fibers result in weak chemical bonding between the fibers and the cementitious material, hindering the application of low-cement-content UHVPC in engineering projects. In addition, the high-temperature resistance and durability of existing UHVPC technologies still need further improvement. Therefore, how to further improve the mechanical strength, high-temperature resistance, and durability of concrete containing steel slag powder has become a key challenge in this field. Summary of the Invention
[0003] The purpose of this invention is to provide an ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface, its preparation method, and its application. The ultra-high performance concrete provided by this invention has superior mechanical strength, high-temperature resistance, and durability.
[0004] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides an ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface, comprising the following components: cement, steel slag powder-based material, silica fume, quartz sand, water, water-reducing agent, modified steel fiber, and nano-silica. The mass ratio of the cement to the steel slag powder-based material is 1:(0.5~0.8). The mass ratio of cement to silica fume is 1:(0.2~0.5). The mass ratio of the cement to the quartz sand is 1:(1.5~2); The mass ratio of cement to water is 1:(0.3~0.4). The mass ratio of cement to water-reducing agent is 1:(0.02~0.03). The mass ratio of the cement to the modified steel fiber is 1:(0.25~0.3). The mass ratio of the cement to nano-silica is 1:(0.03~0.05). The steel slag powder-based material includes mineral powder, steel slag powder, and desulfurized gypsum; the mass ratio of the mineral powder, steel slag powder, and desulfurized gypsum is (50~60):(25~30):(10~20). The modified steel fibers were obtained by stripping plating, surface hydroxylation, and modification with silane coupling agent KH550.
[0005] Preferably, the cement is PⅡ52.5R grade silicate cement.
[0006] Preferably, the particle size of the quartz sand is 10-70 mesh; the quartz sand has a continuous gradation; the mass percentage of each gradation in the quartz sand is: 42-44% for 10-20 mesh, 27-29% for 20-40 mesh, and 28-30% for 40-70 mesh.
[0007] Preferably, the steel fibers in the modified steel fibers are end-hooked steel fibers.
[0008] Preferably, the particle size of the nano-silica is 10~20nm.
[0009] Preferably, the particle size of the steel slag powder-based material is ≥600 mesh.
[0010] Preferably, the SiO2 content in the silica fume is ≥91wt%; and the particle size of the silica fume is ≥600 mesh.
[0011] Preferably, the water-reducing agent is a polycarboxylate high-performance water-reducing agent.
[0012] This invention also provides a method for preparing the ultra-high performance concrete described in the above technical solution, comprising the following steps: (1) Steel fibers and stripping agent are mixed and stripped to obtain stripped steel fibers; the stripped steel fibers are mixed with alkaline solution and surface hydroxylation is performed to obtain hydroxylated steel fibers; the hydroxylated steel fibers are mixed with silane coupling agent hydrolysate and modified, and then cured to obtain modified steel fibers. (2) Mix nano-silica with some water to obtain a nano-silica dispersion; (3) Mix quartz sand, cement, steel slag powder base material and silica fume to obtain a first mixture; mix the first mixture with water-reducing agent, residual water and nano silica dispersion obtained in step (2), and then add modified steel fiber to mix to obtain ultra-high performance concrete; The steps (1) and (2) are not in any particular order.
[0013] The present invention also provides the application of the ultra-high performance concrete described in the above technical solution or the ultra-high performance concrete prepared by the preparation method described in the above technical solution in the construction field.
[0014] This invention provides an ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface, comprising the following components: cement, steel slag powder-based material, silica fume, quartz sand, water, water-reducing agent, modified steel fiber, and nano-silica; the mass ratio of cement to steel slag powder-based material is 1:(0.5~0.8); the mass ratio of cement to silica fume is 1:(0.2~0.5); the mass ratio of cement to quartz sand is 1:(1.5~2); the mass ratio of cement to water is 1:(0.3~0.4); The mass ratio of cement to water-reducing agent is 1:(0.02~0.03); the mass ratio of cement to modified steel fiber is 1:(0.25~0.3); the mass ratio of cement to nano-silica is 1:(0.03~0.05); the steel slag powder-based material includes mineral powder, steel slag powder and desulfurized gypsum; the mass ratio of mineral powder, steel slag powder and desulfurized gypsum is (50~60):(25~30):(10~20); the modified steel fiber is obtained by stripping plating, surface hydroxylation and modification with silane coupling agent KH550 in sequence. This invention uses a large amount of steel slag powder-based material to replace cement, reducing concrete costs. The addition of nano-silica allows it to undergo a secondary hydration reaction with calcium hydroxide in cement hydration products to generate CSH gel, forming a denser internal structure. Simultaneously, nano-silica fills the tiny voids inside the concrete, improving its mechanical strength and other properties. Furthermore, the addition of a silane coupling agent modifies the steel fibers. The "bridging" effect of the silane coupling agent allows the silanols generated after the hydrolysis of the siloxane ends to react with the metal oxides on the surface of the steel fibers, forming strong Si-O-Fe covalent bonds. It is tightly and firmly attached to the fiber surface. On the other hand, the organic functional groups at the ends can chemically react or physically adsorb with hydration products, thereby improving the performance of concrete. By controlling the type of silane coupling agent, KH550 is used. Its hydrolysate is an alkaline solution with higher reactivity and stronger interfacial bridging ability. It can also significantly improve the surface roughness and adhesion of steel fibers. Compared with other coupling agents, it has a better modification effect. By controlling the composition of concrete and the amount of each component, even with a large amount of solid waste such as steel slag powder, the mechanical strength, high temperature resistance and durability of concrete can be improved. Attached Figure Description
[0015] Figure 1 This is a schematic diagram illustrating the testing of concrete compressive strength, splitting tensile strength, flexural strength, and tensile strength according to the present invention. Figure 2 This is a diagram showing the dimensions of the specimen used in the concrete tensile strength test according to the present invention. Figure 3 This is a diagram of the high-temperature testing equipment of the present invention; Figure 4 Images of concrete from Comparative Example 8, Comparative Example 5, Comparative Example 2, and Example 2 after being subjected to a high-temperature test at 400°C; Figure 5 This is a diagram of the sulfate resistance test process. Detailed Implementation
[0016] This invention provides an ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface, comprising the following components: cement, steel slag powder base material, silica fume, quartz sand, water, water-reducing agent, modified steel fiber and nano-silica.
[0017] Unless otherwise specified, the present invention does not have any special limitations on the source of each component, and commercially available products well known to those skilled in the art can be used.
[0018] The ultra-high performance concrete provided by this invention includes cement.
[0019] In this invention, the cement is preferably PⅡ52.5R grade silicate cement.
[0020] The ultra-high performance concrete provided by this invention also includes steel slag powder-based materials.
[0021] In this invention, the particle size of the steel slag powder-based material is preferably ≥600 mesh.
[0022] In this invention, the steel slag powder-based material includes mineral powder, steel slag powder and desulfurized gypsum; the mass ratio of the mineral powder, steel slag powder and desulfurized gypsum is (50~60):(25~30):(10~20), preferably 55:30:15.
[0023] In one embodiment, the composition of the mineral powder may specifically be 45wt% CaO, 35wt% SiO2, 10wt% Al2O3 and 10wt% MgO; the composition of the steel slag powder may specifically be 50wt% CaO, 30wt% Fe2O3, 10wt% CaO and 10wt% MgO.
[0024] In this invention, the mass ratio of cement to steel slag powder is 1:(0.5~0.8). As one embodiment, the mass ratio of cement to steel slag powder can specifically be 1:0.5, 1:0.6, 1:0.7, or 1:0.8. This invention utilizes steel slag powder to replace cement as a binder, which not only reduces the cost of concrete but also solves the resource waste and environmental pollution problems caused by the stockpiling of steel slag powder, realizing the resource utilization of solid waste and meeting the requirements of green environmental protection; controlling the mass ratio of cement to steel slag powder ensures the mechanical strength and other properties of the concrete.
[0025] The ultra-high performance concrete provided by this invention also includes silica fume.
[0026] In this invention, the SiO2 content in the silica fume is preferably ≥91wt%; the particle size of the silica fume is preferably ≥600 mesh.
[0027] In this invention, the mass ratio of cement to silica fume is 1:(0.2~0.5). As one embodiment, the mass ratio of cement to silica fume can specifically be 1:0.2, 1:0.3, 1:0.4, or 1:0.5. This invention incorporates silica fume, utilizing its filling effect and pozzolanic effect to improve the mechanical strength of concrete. By controlling the mass ratio of cement to silica fume, this invention improves various properties of concrete with high solid waste content.
[0028] The ultra-high performance concrete provided by this invention also includes quartz sand.
[0029] In this invention, the particle size of the quartz sand is preferably 10-70 mesh; the quartz sand preferably has a continuous gradation; the mass percentage content of each gradation in the quartz sand is preferably: 42-44% for 10-20 mesh, 27-29% for 20-40 mesh, and 28-30% for 40-70 mesh, more preferably: 43% for 10-20 mesh, 28% for 20-40 mesh, and 29% for 40-70 mesh.
[0030] In this invention, the mass ratio of cement to quartz sand is 1:(1.5~2). As one embodiment, the mass ratio of cement to quartz sand can specifically be 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, or 1:2. By adding quartz sand as fine aggregate and controlling the particle size, gradation composition, and dosage of the quartz sand, this invention can improve various properties of concrete even with high solid waste content.
[0031] The ultra-high performance concrete provided by this invention also includes water.
[0032] In one implementation method, the water used is tap water from a laboratory in Tangshan City.
[0033] In this invention, the mass ratio of cement to water is 1:(0.3~0.4). As one embodiment, the mass ratio of cement to water can specifically be 1:0.3, 1:0.31, 1:0.32, 1:0.33, 1:0.34, 1:0.35, 1:0.36, 1:0.37, 1:0.38, 1:0.39, or 1:0.4. This invention controls the mass ratio of cement to water, resulting in a suitable water-cement ratio in the concrete, thereby improving the mechanical strength of the concrete.
[0034] The ultra-high performance concrete provided by this invention also includes a water-reducing agent.
[0035] In this invention, the water-reducing agent is preferably a polycarboxylate high-efficiency water-reducing agent; the water content of the polycarboxylate high-efficiency water-reducing agent is preferably <3wt%, the pH value is preferably 6~8, and the total alkali content is preferably <5wt%.
[0036] In this invention, the mass ratio of cement to water-reducing agent is 1:(0.02~0.03). As one embodiment, the mass ratio of cement to water-reducing agent can specifically be 1:0.02, 1:0.021, 1:0.022, 1:0.023, 1:0.024, 1:0.025, 1:0.026, 1:0.027, 1:0.028, 1:0.029, or 1:0.03. By adding water-reducing agent and controlling its dosage, this invention ensures that the concrete has suitable fluidity, thereby improving the mechanical strength, high-temperature resistance, and durability of the concrete.
[0037] The ultra-high performance concrete provided by this invention also includes modified steel fibers.
[0038] In this invention, the modified steel fiber is obtained by sequentially stripping plating, surface hydroxylation, and modification with silane coupling agent KH550.
[0039] In this invention, the modified steel fibers are preferably hook-shaped steel fibers; the aspect ratio of the steel fibers is preferably ≥63. As one embodiment, the diameter of the steel fibers is 0.22 mm; the length of the steel fibers is 14 mm. This invention controls the aspect ratio of the steel fibers, providing sufficient anchoring force without significantly reducing the workability of the concrete. The fibers are well dispersed in the concrete, and the hooks at the ends provide additional mechanical interlocking force, improving the toughness of the concrete.
[0040] In this invention, the mass ratio of cement to modified steel fiber is 1:(0.25~0.3). As one embodiment, the mass ratio of cement to modified steel fiber can specifically be 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29 or 1:0.3. This invention modifies steel fibers by adding a silane coupling agent. The "bridging" effect of the silane coupling agent is twofold: firstly, the silanol generated after the hydrolysis of the siloxane end can react with the metal oxides on the surface of the steel fiber to form a strong Si-O-Fe covalent bond, which is tightly and firmly attached to the fiber surface; secondly, the organic functional group end can chemically react with or physically adsorb the hydration products, thereby improving the performance of concrete. By controlling the type of silane coupling agent, KH550 is used, whose hydrolysate is an alkaline solution with higher reactivity and stronger interfacial bridging ability. It can also significantly improve the surface roughness and adhesion of steel fibers, and has a better modification effect compared with other coupling agents. By controlling the mass ratio of cement to modified steel fibers, the mechanical strength, high temperature resistance, and durability of concrete can be improved even with high solid waste content.
[0041] The ultra-high performance concrete provided by this invention also includes nano-silica.
[0042] In this invention, the particle size of the nano-silica is preferably 10~20nm.
[0043] In this invention, the mass ratio of cement to nano-silica is 1:(0.03~0.05). As one embodiment, the mass ratio of cement to nano-silica can specifically be 1:0.03, 1:0.04, or 1:0.05. The addition of nano-silica in this invention allows it to undergo a secondary hydration reaction with calcium hydroxide in the cement hydration products to generate CSH gel, forming a denser internal structure. Simultaneously, nano-silica can fill the tiny voids inside the concrete, improving the mechanical strength, high-temperature resistance, and durability of the concrete. Controlling the mass ratio of cement to nano-silica can improve the mechanical strength, high-temperature resistance, and durability of concrete even with high solid waste content.
[0044] This invention controls the composition of concrete and the amount of each component. With a high amount of solid waste, it improves the mechanical strength, high temperature resistance and durability of concrete. This not only reduces the cost of concrete, but also avoids the problems of resource waste and environmental pollution caused by solid waste dumping.
[0045] This invention also provides a method for preparing the ultra-high performance concrete described in the above technical solution, comprising the following steps: (1) Steel fibers and stripping agent are mixed and stripped to obtain stripped steel fibers; the stripped steel fibers are mixed with alkaline solution and surface hydroxylation is performed to obtain hydroxylated steel fibers; the hydroxylated steel fibers are mixed with silane coupling agent hydrolysate and modified, and then cured to obtain modified steel fibers. (2) Mix nano-silica with some water to obtain a nano-silica dispersion; (3) Mix quartz sand, cement, steel slag powder base material and silica fume to obtain a first mixture; mix the first mixture with water-reducing agent, residual water and nano silica dispersion obtained in step (2), and then add modified steel fiber to mix to obtain ultra-high performance concrete; The steps (1) and (2) are not in any particular order.
[0046] This invention mixes steel fibers and a stripping agent to strip the plating, thereby obtaining stripped steel fibers.
[0047] As one implementation method, the stripping agent is preferably BS-T6 copper alloy stripping agent, purchased from Dongguan Baisite Surface Treatment Raw Materials Co., Ltd., Guangdong Province.
[0048] The present invention does not have a special limitation on the amount of the stripping agent used, as long as it covers the steel fibers.
[0049] In this invention, the stripping temperature is preferably room temperature; the stripping time is preferably 10-20 minutes, more preferably 15 minutes. Steel fibers are prone to rust when directly exposed to air, and are generally coated with a brass layer to protect them. This invention uses a stripping agent to soak the steel fibers, which can remove the oxide layer and brass coating from the steel fiber surface, making subsequent steel fiber modification more beneficial.
[0050] After the plating is removed, the present invention preferably cleans and dries the stripped steel fibers with anhydrous ethanol in sequence.
[0051] The present invention does not have any special limitations on the operation of the anhydrous ethanol cleaning; it is sufficient to clean the stripping agent off the surface of the steel fiber.
[0052] In one implementation method, the drying is air drying.
[0053] After obtaining the stripped steel fibers, the present invention mixes the stripped steel fibers with an alkaline solution and performs surface hydroxylation to obtain hydroxylated steel fibers.
[0054] In this invention, the alkaline solution is preferably an aqueous solution of sodium hydroxide; the mass concentration of the aqueous solution of sodium hydroxide is preferably 15-25%, more preferably 20%.
[0055] The present invention does not have a special limitation on the amount of alkaline solution used, as long as it can cover the steel fibers after stripping.
[0056] In this invention, the surface hydroxylation temperature is preferably room temperature; the surface hydroxylation time is preferably 25-35 minutes, more preferably 30 minutes. Surface hydroxylation in this invention is more conducive to subsequent modification processes.
[0057] After surface hydroxylation is completed, the present invention preferably cleans and dries the surface-hydroxylated steel fibers with anhydrous ethanol in sequence.
[0058] The present invention does not have any special limitations on the operation of the anhydrous ethanol cleaning; it is sufficient to clean the alkaline solution off the surface of the steel fiber.
[0059] In one implementation method, the drying is air drying.
[0060] After obtaining hydroxylated steel fibers, the present invention mixes the hydroxylated steel fibers with a silane coupling agent hydrolysate, performs modification treatment, and then cures them to obtain modified steel fibers.
[0061] In this invention, the silane coupling agent hydrolysate is prepared by silane coupling agent KH550, ethanol and water; the mass ratio of ethanol to water is preferably (2~4):1, more preferably 3:1; the mass concentration of silane coupling agent KH550 in the silane coupling agent hydrolysate is preferably 5~15%, more preferably 8~10%.
[0062] The present invention does not have a special limitation on the amount of the silane coupling agent hydrolysate, as long as it is sufficient to cover the hydroxylated steel fibers.
[0063] In this invention, the temperature of the modification treatment is preferably 75~85℃, more preferably 80℃; the time of the modification treatment is preferably 40~50min, more preferably 45min; and the modification treatment is preferably carried out under stirring conditions. This invention does not impose any special limitations on the stirring method and rate; any technical solution well known to those skilled in the art can be used.
[0064] In this invention, the curing temperature is preferably 100~120℃, more preferably 110℃; the curing time is preferably 0.5~1.5h, more preferably 1h. By performing curing and controlling the curing temperature and time, this invention enables the silane coupling agent to be cured into a coating on the surface of steel fibers.
[0065] This invention controls the specific modification process and parameters of steel fibers, which can further improve the modification effect and thus further improve the mechanical strength and other properties of concrete.
[0066] This invention involves mixing nano-silica with a portion of water to obtain a nano-silica dispersion.
[0067] In this invention, the mass of the water portion is preferably 45-55% of the total mass of water, more preferably 50%.
[0068] In this invention, the mixing of the nano-silica and a portion of the water is preferably carried out under stirring conditions; the stirring speed is preferably 40-60 rpm, more preferably 50 rpm; the mixing time is preferably 10-20 min, more preferably 15 min.
[0069] After obtaining the modified steel fiber and nano-silica dispersion, the present invention mixes quartz sand, cement, steel slag powder-based material and silica fume to obtain a first mixture; the first mixture is mixed with water-reducing agent, residual water and the nano-silica dispersion, and then the modified steel fiber is added and mixed to obtain ultra-high performance concrete.
[0070] In this invention, the mixing of the quartz sand, cement, steel slag powder-based material, and silica fume is preferably carried out under stirring conditions; the mixing time is preferably 4-6 minutes, more preferably 5 minutes. This invention does not impose any special limitation on the stirring speed; stirring techniques well-known to those skilled in the art can be used.
[0071] In this invention, the mixing of the first mixture with the water-reducing agent, residual water, and the nano-silica dispersion is preferably carried out under stirring conditions; the mixing time is preferably 5-15 minutes, more preferably 10 minutes. This invention does not impose any special limitation on the stirring speed; stirring techniques well-known to those skilled in the art can be used.
[0072] In this invention, the mixing time for adding modified steel fibers is preferably 4-6 minutes, more preferably 5 minutes; the mixing is preferably carried out under stirring conditions. This invention does not impose any special limitation on the stirring speed; stirring techniques well-known to those skilled in the art can be used.
[0073] The present invention also provides the application of the ultra-high performance concrete described in the above technical solution or the ultra-high performance concrete prepared by the preparation method described in the above technical solution in the construction field.
[0074] The present invention does not impose any special limitations on the operation of the application, and any technical solution known to those skilled in the art can be used.
[0075] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0076] The cement used in all embodiments and comparative examples is PⅡ52.5R grade Portland cement; The steel slag powder-based material has a particle size of ≥600 mesh and is composed of mineral powder, steel slag powder and desulfurized gypsum in a mass ratio of 55:30:15. The silica fume has a particle size of ≥600 mesh and a SiO2 content of 91 wt%. The quartz sand has a particle size of 10-70 mesh and a continuous gradation. The mass percentage of each gradation is as follows: 10-20 mesh 43%, 20-40 mesh 28%, and 40-70 mesh 29%. The water used was tap water from the Tangshan City Laboratory. The water-reducing agent is a polycarboxylate high-efficiency water-reducing agent; The steel fibers are hook-shaped steel fibers with a diameter of 0.22 mm and a length of 14 mm; The particle size of nano-silica is 10~20nm.
[0077] Example 1 An ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface is composed of the following components: cement, steel slag powder base material, silica fume, quartz sand, water, water-reducing agent, modified steel fiber and nano-silica. The mass ratio of cement to steel slag powder-based material is 1:0.7; the mass ratio of cement to silica fume is 1:0.3; the mass ratio of cement to quartz sand is 1:2; the mass ratio of cement to water is 1:0.32; the mass ratio of cement to water-reducing agent is 1:0.025; the mass ratio of cement to modified steel fiber is 1:0.3; and the mass ratio of cement to nano-silica is 1:0.04. The preparation method of the ultra-high performance concrete is as follows: (1) Steel fibers and stripping solution are mixed, stripped at room temperature for 15 min, cleaned with anhydrous ethanol and air-dried to obtain stripped steel fibers; stripped steel fibers and sodium hydroxide aqueous solution (mass concentration of 20%) are mixed, surface hydroxylation is performed at room temperature for 30 min, cleaned with anhydrous ethanol and air-dried to obtain hydroxylated steel fibers; hydroxylated steel fibers and silane coupling agent hydrolysate (prepared by KH550, ethanol and water, with a mass ratio of ethanol to water of 3:1 and a mass concentration of KH550 of 8%) are mixed, stirred at 80℃ water bath temperature for 45 min for modification treatment, and then placed in 110℃ oven for curing for 1 h, and cooled to room temperature to obtain modified steel fibers; (2) Stir nano-silica and a portion of water (50% of the total mass of water) at 50 rpm for 15 min to obtain a nano-silica dispersion; (3) Put quartz sand, cement, steel slag powder base material and silica fume into a mixer and mix for 5 minutes. Then add water-reducing agent, residual water and nano silica dispersion, mix for 10 minutes, and then add modified steel fiber and mix for 5 minutes to obtain ultra-high performance concrete.
[0078] Example 2 An ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface is different from Example 1 in that the mass concentration of KH550 is 10%, while all other aspects are the same as Example 1.
[0079] Example 3 An ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface is different from Example 1 in that the mass concentration of KH550 is 12%, while all other aspects are the same as Example 1.
[0080] Comparative Example 1 A type of concrete, differing from Example 1 only in that it does not contain nano-silica; otherwise, it is identical to Example 1.
[0081] Comparative Example 2 A type of concrete, differing from Example 2 only in that it does not contain nano-silica; otherwise, it is identical to Example 2.
[0082] Comparative Example 3 A type of concrete, which differs from Example 3 in that it does not contain nano-silica, but is otherwise identical to Example 3.
[0083] Comparative Example 4 An ultra-high performance concrete using steel slag powder containing nano-silica is composed of the following components: cement, steel slag powder-based materials, silica fume, quartz sand, water, water-reducing agent, unmodified steel fiber, and nano-silica. The mass ratio of cement to steel slag powder-based material is 1:0.7; the mass ratio of cement to silica fume is 1:0.3; the mass ratio of cement to quartz sand is 1:2; the mass ratio of cement to water is 1:0.32; the mass ratio of cement to water-reducing agent is 1:0.025; the mass ratio of cement to unmodified steel fiber is 1:0.3; and the mass ratio of cement to nano-silica is 1:0.02. The preparation method of the ultra-high performance concrete is as follows: (1) Nano silica and part of water (50% of the total mass of water) are stirred at 50 rpm for 15 min to obtain nano silica dispersion. (2) Place quartz sand, cement, steel slag powder base material and silica fume into a mixer and mix for 5 minutes. Then add water-reducing agent, residual water and nano silica dispersion, mix for 10 minutes, and then add unmodified steel fiber and mix for 5 minutes to obtain ultra-high performance concrete.
[0084] Comparative Example 5 A type of concrete differs from Comparative Example 4 in that the mass ratio of cement to nano-silica is 1:0.04, while all other aspects are the same as Comparative Example 4.
[0085] Comparative Example 6 A type of concrete differs from Comparative Example 4 in that the mass ratio of cement to nano-silica is 1:0.06, while all other aspects are the same as Comparative Example 4.
[0086] Comparative Example 7 An ultra-high performance concrete containing steel slag powder is composed of the following components: cement, steel slag powder-based materials, silica fume, quartz sand, water, water-reducing agent and unmodified steel fiber; The mass ratio of cement to steel slag powder-based material is 1:0.42; the mass ratio of cement to silica fume is 1:0.25; the mass ratio of cement to quartz sand is 1:1.67; the mass ratio of cement to water is 1:0.27; the mass ratio of cement to water-reducing agent is 1:0.021; and the mass ratio of cement to unmodified steel fiber is 1:0.25. The preparation method of the ultra-high performance concrete is as follows: (1) Mix the water-reducing agent and part of the water (70% of the total mass of water) for 15 minutes to obtain the water-reducing agent dispersion; (2) Put quartz sand, cement, steel slag powder base material and silica fume into a mixer and mix for 5 minutes. Then add water-reducing agent dispersion and mix for 10 minutes. When the concrete is in flake form, add the remaining water and continue mixing for 10 minutes. Then add unmodified steel fiber and mix for 5 minutes to obtain ultra-high performance concrete.
[0087] Comparative Example 8 A type of concrete differs from Comparative Example 7 in that the mass ratio of cement to steel slag powder is 1:0.7; the mass ratio of cement to silica fume is 1:0.3; the mass ratio of cement to quartz sand is 1:2; the mass ratio of cement to water is 1:0.32; the mass ratio of cement to water-reducing agent is 1:0.025; and the mass ratio of cement to unmodified steel fiber is 1:0.3. All other aspects are the same as in Comparative Example 7.
[0088] Comparative Example 9 A type of concrete differs from Comparative Example 7 in that the mass ratio of cement to steel slag powder is 1:1.125; the mass ratio of cement to silica fume is 1:0.375; the mass ratio of cement to quartz sand is 1:2.5; the mass ratio of cement to water is 1:0.4; the mass ratio of cement to water-reducing agent is 1:0.031; and the mass ratio of cement to unmodified steel fiber is 1:0.37. All other aspects are the same as in Comparative Example 7.
[0089] According to the "Standard for Test Methods of Ultra-High Performance Concrete" (T / CECS 864-2021), the compressive strength, splitting tensile strength, flexural strength, and tensile strength of the concrete in Examples 1-3 and Comparative Examples 1-9 were tested respectively. The test schematic diagrams are shown below. Figure 1 As shown ( Figure 1 The first row from left to right shows the compressive strength and splitting tensile strength tests, and the second row from left to right shows the flexural strength and tensile strength tests. The test results are shown in Table 1.
[0090] The compressive strength testing equipment used was the YAS-5000 microcomputer-controlled electro-hydraulic servo pressure testing machine manufactured by Jilin Guanteng Automation Technology Co., Ltd., with a maximum range of 500kN. Continuous and uniform loading was employed using the test force method at a loading rate of 1.0MPa / s. Three 100mm×100mm×100mm cubic specimens were used as parallel specimens, and the arithmetic mean of the three specimens was taken as the compressive strength value of the group of specimens, accurate to 0.01MPa. The compressive strength was calculated according to Formula 1: Formula 1, In Equation 1: The compressive strength (MPa) of ultra-high performance concrete is calculated to an accuracy of 0.01 MPa. The failure load of the specimen (N); The bearing area of the specimen (mm²) 2 ).
[0091] The splitting tensile strength test also used three 100mm×100mm×100mm cube specimens as parallel specimens. The arithmetic mean of the three specimens was taken as the compressive strength value of the group of specimens, accurate to 0.01MPa. A continuous uniform loading method was used, with a loading rate of 0.11MPa / s. The splitting tensile strength was calculated according to Equation 2: Equation 2, In Equation 2: The splitting tensile strength (MPa) of ultra-high performance concrete is calculated to an accuracy of 0.01 MPa. The failure load of the specimen (N); The area of the splitting surface of the specimen (mm²) 2 ).
[0092] Bending strength testing was performed using three prism specimens (100mm × 100mm × 400mm), with three specimens per group. The arithmetic mean of the three specimens was taken as the bending strength value of that group, accurate to 0.01 MPa. Continuous uniform loading was applied using a displacement loading method at a loading rate of 0.2 mm / min. The bending strength was calculated according to Equation 3: Formula 3, In Equation 3: The flexural strength (MPa) of ultra-high performance concrete is calculated to an accuracy of 0.01 MPa. The maximum load (N) during the bending test. The span between the test beam supports (mm); Width of the specimen cross-section (mm); The height of the specimen cross section is (mm).
[0093] For the test of bending toughness, the initial bending toughness ratio is used. Characterizes the flexural toughness of concrete before it reaches its peak deflection. Calculate according to Equation 4: Equation 4, In Equation 4: The flexural strength of concrete (MPa); This represents the equivalent initial flexural strength of the concrete (MPa). Calculate according to Equation 5: Equation 5, In Equation 5: Peak deflection The area under the load-deflection curve.
[0094] With residual flexural toughness ratio Characterizes the residual flexural toughness of concrete after it reaches its peak deflection. Calculate according to Equation 6: Formula 6, In Equation 6: The flexural strength of concrete (MPa); It represents the equivalent residual flexural strength of concrete (MPa). Calculate according to Equation 7: Equation 7, In Equation 7: Peak deflection to The area under the load-deflection curve corresponding to the segment; for to The mid-span deflection value (mm) of the segment is calculated according to Equation 8: Formula 8, In Equation 8: Calculate the deflection for a given mid-span. Due to the span between the specimen supports L=300mm, to fully reflect the residual bearing capacity of the specimen after reaching the peak load, and because the total deflection of some specimens in the 12 sets of examples and comparative examples did not exceed 3mm, the present invention... The value is set to 150.
[0095] For the tensile strength test, three parallel specimens were set up in each group. A continuous uniform loading method was used, employing displacement loading at a speed of 0.2 mm / min. The specimen dimensions are as follows: Figure 2 As shown. Tensile strength is calculated according to Equation 9: Formula 9, In Equation 9: The tensile strength (MPa) is calculated to an accuracy of 0.01 MPa. The maximum load (N) during the tensile test loading process; The cross-sectional area (mm²) of the middle section of the tensile specimen. 2 ).
[0096] Table 1 Mechanical properties of concrete in Examples 1-3 and Comparative Examples 1-9
[0097] As shown in Table 1, under standard curing conditions, the compressive strength and splitting tensile strength of each group of examples and comparative examples showed a positive correlation with the curing age. In comparative examples 7-9, the mechanical properties of the three comparative examples showed a negative correlation with the amount of steel slag powder added.
[0098] During the 7-day curing period after adding water, cement preferentially undergoes a hydration reaction, and AI is released from the C3A in the cement. 3+ Ca dissolved from desulfurization gypsum in steel slag powder 2+ and SO4 2- The reaction generates a large number of needle-like or short columnar AFt crystals, forming a dense framework. On the other hand, C3S in the cement reacts intensely upon contact with water, generating a large amount of CSH gel and CH crystals on its surface, forming a dense strength framework. The combined effect of these two factors gives Comparative Example 7 its strong early-stage strength and lays the foundation for later strength development. Furthermore, silica fume can also undergo a hydration reaction with CH crystals to generate CSH gel with a low calcium-to-silica ratio. However, in the later stages of curing, the compressive strength of Comparative Examples 8 and 9 both reached over 120 MPa. This is because the reduced cement dosage lowered early-stage water consumption, providing the necessary moisture for the subsequent hydration reaction of the mineral powder in the steel slag powder. As the cement hydration reaction occurs, the pH value of the cementitious system increases, and the OH-... -The ions break the Si-O-Si and Al-O-Si bonds in the mineral powder glass, releasing [SiO4]. 4- and [AIO4] 5- Ions, under the co-excitation of CH and gypsum, form CSH gel and AFt crystals. The continuous dissolution of desulfurized gypsum continuously replenishes SO4. 2- The ion content inhibits the conversion of AFt to AFm. Simultaneously, the CH crystals produced during early cement hydration can react with the active SiO2 in silica fume to generate CSH gel with a low calcium-to-silica ratio. In summary, although the early strength decreases after steel slag powder replaces cement by mass, the CSH gel, CH crystals, and AFt crystals produced during early cement hydration still provide sufficient strength and create conditions for subsequent hydration reactions of mineral powder and silica fume, thus providing the possibility for the later strength development of embodiments with high steel slag powder content. Taking all factors into consideration, Comparative Example 8 was ultimately selected as the baseline group for this invention.
[0099] Comparative Examples 4-6 were based on Comparative Example 8 with different amounts of nano-silica added. Table 1 shows that the mechanical properties of the three comparative examples initially increased and then decreased with increasing nano-silica content. Comparative Example 5 showed the most significant strength improvement, with its 28-day compressive strength increasing by approximately 2.9%. At lower nano-silica content, it can act as micro-aggregate filling the nanoscale pores between mineral powder and CSH gel. Simultaneously, nano-silica exhibits extremely high activity, rapidly reacting with CH crystals generated during cement hydration to produce a large amount of CSH gel. This not only develops early strength but also provides nucleation sites for subsequent secondary hydration of mineral powder, further ensuring the development of later-stage strength. However, the compressive strength of Comparative Example 6 decreased by about 4.5% compared to Comparative Example 8 after 28 days of curing. This is because the specific surface area of nano-silica is huge. When the amount of nano-silica is too large, it will absorb water severely, which will seriously affect the workability of concrete and cause more pores in the early stage of mixing. In addition, too much nano-silica particles will have an agglomeration effect, resulting in weak areas inside the concrete. Under the combined influence of these two factors, the mechanical properties of the concrete will decrease.
[0100] Unlike Comparative Examples 4-6, Comparative Examples 1-3 did not incorporate nano-silica. Instead, they used silane coupling agent hydrolysates prepared with different amounts of ethanol, water, and KH550 to modify steel fibers and prepare concrete. Table 1 shows that the mechanical properties of Comparative Examples 1-3 exhibited the same trend as Comparative Examples 4-6, but the underlying mechanisms differed fundamentally. When the KH550 concentration was low, during curing, the ethoxy group at one end of its molecular structure hydrolyzed into silanol groups (Si-OH), which could condense with the iron hydroxyl groups (Fe-OH) on the steel fiber surface to form strong Fe-O-Si bonds, anchoring itself to the fiber. The other end, containing an amino group (-NH2), could chemically bond or strongly hydrogen-bond with products such as CSH gel generated during cement hydration, inhibiting the aggregation of CH crystals on the steel fiber surface and preventing weak areas. Furthermore, the modified steel fibers had reduced surface energy and a smaller contact angle with the cement paste, allowing for better dispersion in the concrete aggregate and preventing stress concentration. However, the 28-day compressive strength of Comparative Example 3 was 3.8% lower than that of Comparative Example 8. The reason is that the excessive KH550 cannot form chemical bonds on the surface of the steel fiber. It can only be loosely accumulated in the first layer through van der Waals forces, thus forming a "weak boundary layer". At the same time, the silanols generated by the hydrolysis of KH550 tend to condense with each other to form Si-O-Si bonds rather than bond on the surface of the steel fiber. These free particles will form defects or micro-cavities in the cement paste and will also hinder the bonding between the fiber and the matrix on the surface of the steel fiber, thus leading to a decrease in concrete strength.
[0101] Examples 1-3, based on Comparative Examples 1-3, added the same amount of nano-silica as Comparative Example 5. The mechanical properties at 28 days also showed a trend of initial enhancement followed by weakening. Since the three examples added the same amount of nano-silica, when the KH550 concentration was low, the functional groups at both ends of KH550 played a role, enhancing the mechanical properties of concrete under the combined action of KH550 and nano-silica. The 28-day compressive strength of Example 3 was 14.9% lower than that of Comparative Example 8. This is because the addition of nano-silica increases the water required for KH550 hydrolysis, preventing the formation of effective chemical bonds on the steel fiber surface. Simultaneously, the "weak boundary layer" formed by excessive KH550 further weakened the bond between the matrix and the steel fiber surface, leading to a decrease in concrete strength.
[0102] The equivalent initial bending strength, initial bending toughness ratio, equivalent residual bending strength, and residual bending toughness ratio of Examples 1-3 and Comparative Examples 1-9 were calculated according to Formulas 4-8. The calculation results are shown in Table 2.
[0103] Table 2. Bending toughness of each embodiment and comparative example
[0104] As can be seen from Table 2, although the initial bending toughness ratio of Example 2 is the same as that of Comparative Example 8, and the residual bending toughness ratio is smaller than that of Comparative Example 8, combined with the data in Table 1, the peak bending load of Example 2 is higher than that of Comparative Example 8, and the area enclosed by the load-deflection curve before reaching the peak load is also larger than that of Comparative Example 8, indicating that Example 2 has stronger toughness than Comparative Example 8.
[0105] Based on the mechanical properties of the above 12 sets of examples and comparative examples, Example 2, Comparative Example 2, Comparative Example 5, and Comparative Example 8 were selected for high-temperature testing. To prevent the specimens from cracking and damaging the experimental equipment due to excessive moisture content after curing, the cured specimens were placed in a 105°C forced-air drying oven for 72 hours before high-temperature firing to remove as much internal moisture as possible. After drying, the specimens were allowed to cool naturally to room temperature. The high-temperature test was conducted by raising the oven temperature to the predetermined temperature at a rate of 5°C / min, and then holding the temperature for 120 minutes. Afterward, the specimens were removed and allowed to cool naturally to room temperature. The high-temperature testing equipment was as follows: Figure 3 As shown.
[0106] All four groups of concrete specimens remained intact after being subjected to a high temperature of 200℃. Compressive strength tests were conducted on all four groups using the same experimental protocol, and the results are shown in Table 1. Based on the experimental data in Table 1, the compressive strength of all four groups increased after being subjected to a high temperature of 200℃. Specifically, Comparative Example 8 showed an increase of approximately 12.9%, and Example 2 showed an increase of approximately 24.4%, both still 11.5% higher than Comparative Example 8. This can be attributed to two main reasons: firstly, the high temperature of 200℃ further stimulated the unhydrated cement and mineral powder in the concrete cementitious system. In Comparative Example 8, further hydration reactions promoted the production of small amounts of hydration products such as CH crystals, resulting in a denser pore structure in the matrix; secondly, at this temperature, free water and adsorbed water evaporated slowly, without significant vapor pressure damage. In Example 2, the further reduction of the matrix pores forms tiny nanopores, which can be filled more fully by nano-silica. The modified steel fiber is more firmly bonded to the matrix, and the bridging effect of the fiber is more significant. The combined effect of these two factors allows Example 2 to still have high strength after being heated to 200°C.
[0107] In addition, high-temperature tests at 400°C were conducted on Examples 2, 2, 5, and 8. However, after being burned at this temperature, the specimens in Comparative Examples 5 and 2 all exploded and could not continue to complete the compressive and splitting tensile strength tests. Figure 4As shown in Table 1, after being burned at 400℃, the compressive strength of Comparative Example 8, which remained intact, decreased by 7.8% compared to that at 200℃, while the splitting tensile strength increased by 9.9%. In contrast, Example 2, which incorporated both nano-silica and modified fibers, showed increases in compressive strength and splitting tensile strength of 11.84% and 2.5%, respectively. Compared to Comparative Example 8, Example 2 exhibited significantly better high-temperature resistance.
[0108] Table 3 shows the mass loss of concrete after high temperature in some examples.
[0109] As shown in Table 3, at 200℃, the mass loss rate of each group of samples ranged from -1% to 2.5%, which was at a low level. A longitudinal comparison revealed a negative increase in the mass loss of Comparative Example 8, indicating an increase in its mass. This suggests that after being calcined at 200℃, further hydration reactions occurred internally, generating hydration products such as AFt and CH crystals, thus increasing its compressive and splitting tensile strengths after 200℃. However, the strength increase in Comparative Example 2 was limited. This is because although Example 2 experienced a slight mass loss after being calcined at 200℃, the cement and mineral powder within it further hydrated at high temperatures. The resulting CSH flocculent products further filled some of the tiny pores caused by the incorporation of nano-silica, thus preventing a decrease in strength despite the mass loss in Example 2.
[0110] At 200~400℃, the mass loss increased significantly, with Comparative Example 8 showing a mass loss of 6.17%. This was mainly due to the large-scale dehydration and decomposition of the matrix hydration products, resulting in the loss of a large amount of interlayer water and chemically bound water. The structure of the hydration products gradually became loose, which was the main reason for the mass loss at this temperature gradient. At this temperature, the nano-silica and the water bound to it may begin to undergo hydration reactions, and the hydration products such as Aft, CH crystals and CSH gel increased, which further improved the strength.
[0111] The mechanical properties and mass loss after high-temperature burning effectively demonstrate that the ultra-high performance concrete containing steel slag powder modified by the interface of nano-silica and fiber can still maintain relatively good structural stability under high-temperature conditions.
[0112] To more fully investigate the durability of the concrete described in this invention, sulfate resistance tests were conducted on Example 2, Comparative Example 2, Comparative Example 5 and Comparative Example 8 in accordance with the "Standard for Test Methods of Long-Term Performance and Durability of Concrete" (GBT 50082-2024).
[0113] Sulfate resistance tests were conducted using 100mm×100mm×100mm cubic specimens. Two days before the completion of the 28-day standard curing period, the specimens were removed from the curing room, their surface moisture was wiped off, and they were placed in a drying oven at 80±5℃ for 48 hours. After drying, the specimens were removed and cooled to room temperature. The specimens were then immersed in a prepared 10wt% sodium sulfate solution for 48 hours, followed by natural air drying for 10 hours, and then placed in a drying oven at 80±5℃ for 12 hours. After drying, the specimens were removed and cooled to room temperature within 2 hours. This 72-hour cycle constituted one wet-dry cycle. The test procedure was as follows. Figure 5 As shown ( Figure 5 (a) shows soaking, (b) shows air drying, and (c) shows oven drying. The concrete quality, compressive strength, and sulfate ion content were measured after every 5 cycles. The results after the 5th and 10th cycles are shown in Table 4. The experiment continued until 40 wet-dry cycles were completed. In addition, a control group of test blocks under standard curing conditions was set up. Based on the existing test results in Table 4, a gray-scale prediction model was used to predict the test results of Example 2, Comparative Example 2, Comparative Example 5, and Comparative Example 8 after 40 sulfate wet-dry cycles. As shown in Table 5, after 40 sulfate wet-dry cycles, the strength of Comparative Example 8 decreased to 99.56 MPa, below 100 MPa, while the compressive strength of Comparative Example 2 and Comparative Example 5 were similar, with Example 2 having the highest strength. This indicates that the addition of nano-silica or the use of modified steel fibers can, to a certain extent, improve the sulfate resistance of ultra-high performance concrete containing steel slag powder.
[0114] Table 4 shows the test results of some concrete resistance to sulfate attack.
[0115] Table 5 shows the predicted results of 40 sulfate wet-dry cycles for some concrete.
[0116] Table 4 shows that after five wet-dry cycles, all four test groups exhibited strength increases, with Comparative Example 2 and Comparative Example 8 showing increases of 28.9% and 28.7%, respectively. This is because sulfate ions react with CH crystals and hydrated calcium aluminate on the concrete surface to form Aft crystals, optimizing the pore structure and thus increasing strength. The decrease in strength after ten wet-dry cycles is due to the increased sulfate concentration in the pore solution during the soaking stage. The higher concentration difference creates osmotic pressure, causing internal water to migrate to the surface. The drying stage causes salt precipitation, with crystallization pressures reaching tens or even hundreds of megapascals, far exceeding the interfacial bonding force between the fiber and the matrix, leading to internal structural damage and reduced strength. This indicates that simply optimizing the fiber-interfacial bonding performance has limited effect on improving the concrete's resistance to sulfate attack. Comparative Example 5, with a strength increase of only 19.3% after five wet-dry cycles, lower than Comparative Examples 2 and 8, further supports this point. In Example 2, after 5 cycles, the strength increase was only 9.9%, indicating that by incorporating nano-silica to optimize the matrix pore structure, it is possible to effectively prevent sulfate ions from eroding the interior of concrete and prevent the formation of internal Aft crystals.
[0117] After 10 wet-dry cycles, Comparative Examples 2, 5, and 8 all showed a decrease in strength, indicating that the excessive formation of Aft crystals had led to an increase in microcracks within the concrete. This further demonstrates that simply optimizing the fiber-matrix interfacial bond and pore structure alone has limited effect on improving the concrete's resistance to sulfate attack. In contrast, Example 2 showed an increase in strength after 10 wet-dry cycles, indicating that simultaneously optimizing the matrix microstructure and fiber-matrix interfacial bond performance can effectively improve the concrete's resistance to sulfate attack.
[0118] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. An ultra-high performance concrete containing steel slag powder modified with nano-silica and fiber interface, comprising the following components: cement, steel slag powder-based material, silica fume, quartz sand, water, water-reducing agent, modified steel fiber and nano-silica; The mass ratio of the cement to the steel slag powder-based material is 1:(0.5~0.8). The mass ratio of cement to silica fume is 1:(0.2~0.5). The mass ratio of cement to quartz sand is 1:(1.5~2); The mass ratio of cement to water is 1:(0.3~0.4). The mass ratio of cement to water-reducing agent is 1:(0.02~0.03). The mass ratio of the cement to the modified steel fiber is 1:(0.25~0.3). The mass ratio of the cement to nano-silica is 1:(0.03~0.05). The steel slag powder-based material includes mineral powder, steel slag powder, and desulfurized gypsum; the mass ratio of the mineral powder, steel slag powder, and desulfurized gypsum is (50~60):(25~30):(10~20). The modified steel fibers were obtained by stripping plating, surface hydroxylation, and modification with silane coupling agent KH550.
2. The ultra-high performance concrete according to claim 1, characterized in that, The cement is PⅡ52.5R grade silicate cement.
3. The ultra-high performance concrete according to claim 1, characterized in that, The quartz sand has a particle size of 10-70 mesh; the quartz sand has a continuous gradation; the mass percentage of each grade in the quartz sand is: 42-44% for 10-20 mesh, 27-29% for 20-40 mesh, and 28-30% for 40-70 mesh.
4. The ultra-high performance concrete according to claim 1, characterized in that, The modified steel fibers are end-hooked steel fibers.
5. The ultra-high performance concrete according to claim 1, characterized in that, The particle size of the nano-silica is 10~20nm.
6. The ultra-high performance concrete according to claim 1, characterized in that, The particle size of the steel slag powder-based material is ≥600 mesh.
7. The ultra-high performance concrete according to claim 1, characterized in that, The silica fume contains ≥91wt% SiO2; the particle size of the silica fume is ≥600 mesh.
8. The ultra-high performance concrete according to claim 1, characterized in that, The water-reducing agent is a polycarboxylate high-performance water-reducing agent.
9. A method for preparing ultra-high performance concrete according to any one of claims 1 to 8, comprising the following steps: (1) Steel fibers and stripping agent are mixed and stripped to obtain stripped steel fibers; the stripped steel fibers are mixed with alkaline solution and surface hydroxylation is performed to obtain hydroxylated steel fibers; the hydroxylated steel fibers are mixed with silane coupling agent hydrolysate and modified, and then cured to obtain modified steel fibers. (2) Mix nano-silica with some water to obtain a nano-silica dispersion; (3) Mix quartz sand, cement, steel slag powder base material and silica fume to obtain a first mixture; mix the first mixture with water-reducing agent, residual water and nano silica dispersion obtained in step (2), and then add modified steel fiber to mix to obtain ultra-high performance concrete; The steps (1) and (2) are not in any particular order.
10. The application of the ultra-high performance concrete according to any one of claims 1 to 8 or the ultra-high performance concrete prepared by the preparation method according to claim 9 in the field of construction.